1990
DOI: 10.1093/nar/18.16.4817
|View full text |Cite
|
Sign up to set email alerts
|

A yeast homolog of the human UEF stimulates transcription from the adenovirus 2 major late promoter in yeast and in mammalian cell-free systems

Abstract: We report the identification and purification of a yeast factor functionally homologous to the human upstream element factor (UEFh). Although the yeast protein (UEFy) has a higher molecular weight than the HeLa UEF (60 kD versus 45 kD) both have identical DNA-binding properties: the purified UEFy recognizes the Adenovirus 2 (Ad2) major late promoter upstream element (MLP-UE; from nucleotide -49 to -67) as well as the IVa2 upstream element (IVa2-UE; from nucleotide -98 to -122) with a higher affinity for the ML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Ternary and higher-order complexes of Cbf1p Figure 2B demonstrates that, as has also been reported by others (see Bram and Kornberg 1987;Moncollin et al 1990), Cbf1p can be reversibly denatured, and all subforms regain the ability to dimerize and to bind DNA upon renaturation. We made use of this observation to study whether additional proteins associate with the various Cbf1p/DNA complexes.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Ternary and higher-order complexes of Cbf1p Figure 2B demonstrates that, as has also been reported by others (see Bram and Kornberg 1987;Moncollin et al 1990), Cbf1p can be reversibly denatured, and all subforms regain the ability to dimerize and to bind DNA upon renaturation. We made use of this observation to study whether additional proteins associate with the various Cbf1p/DNA complexes.…”
Section: Resultssupporting
confidence: 83%
“…Mellor et al (1991) demonstrated that the puri®ed 37-and 54-kDa forms of Cbf1p can form all three possible dimers. The occurrence of Cbf1 as a protein of variable length was interpreted as resulting from unspeci®c proteolysis, since incubation of the native full-length protein with proteinase K gave rise to polypeptide fragments of Cbf1p similar to those found in vivo (Moncollin et al 1990). Interestingly, more than one signal can be observed in EMSAs performed with Cbf1p synthesized in vitro or in E. coli (Mellor et al 1991;this work).…”
Section: Introductionmentioning
confidence: 99%
“…These CDEI-like sequences exhibit a certain variation at positions 1 and 2, which allows speculation that at these sites, CPF1 may bind together with another protein as heterodimer, or that completely different proteins bind. Recently, a yeast homolog of the human upstream element factor (UEFh), UEFy, was purified and shown to bind to a sequence carrying CACRTG in its central part and to activate transcription (37). Either UEFy is identical to CPF1 or it represents some member of the yeast CDEI-like sequence-binding proteins (11,18,42,49).…”
Section: Resultsmentioning
confidence: 99%
“…28S, GGAATCCTGGT-TAGTTTCTTTTCCTCCGCT. UE sequence derived from Moncollin et al (1990), GGTGTAGGCCACGTGAC CGGGTGT and its complementary strand ACACCCGGT-CACGTGGCCTACACC.…”
Section: Oligonucleotidesmentioning
confidence: 99%